(untitled) (Bangladesh Journal of Medical Science, 2021)
Background: Laparoscopic Cholecystectomy has now become a better option instead of the Open Cholecystectomy for treatment of Cholelithiasis that it has been a gold standard for the Cholelithiasis condition throughout the Globe. Last century was the most fruitful era for the treatment of the biliary tract disease as it has already proved the progress from the open to laparoscopic surgery with a single port surgery. Methods: The purpose of our study is to grading of the Laparoscopic Cholecystectomy in Acute Cholecystits and has been studying the outcome of problematic and challenging Laparoscopic Cholecystectomy cases, its’ complication (s) and management to decide when to converting Laparoscopic Cholecystectomy to Open Cholecystectomy. The study analyzes the conversion rate of Laparoscopic Cholecystectomy in the Ibn Sina Medical College, Kallyanpur, Dhaka, Bangladesh. This is a retrospective study of 150 patients (Male - 75% and Female - 25%) which was conducted during the period from January 2015 to January 2017. Results: Out of the 150 cases 140 (93%) had been successfully operated by Laparoscopic Cholecystectomy. And, only 10 (7%) cases (out of a total of 150) got converted from the Laparoscopic to Open Cholecystectomy and they belonged to Grade - E with severely contracted gallbladder, morbid adhesion, short cystic duct and bile duct injury. Conclusions: The Laparoscopic Cholecystectomy has familiar as a unique procedure of choice for the management of symptomatic gall bladder. Laparoscopic Cholecystectomy intra operatively for grade A to E where Grade A is very easy level to perform Gall Bladder Surgery to Grade E where conversion is 115% due to bad. Bangladesh Journal of Medical Science Vol.20(2) 2021 p.318-322